The Impact of Efficiency of Working Capital Management on Company Profitability - Wahyuningsih, Mutia; Sihombing, Pardomuan; Indira Puspa Gustiah (International Journal of Entrepreneurship and Business Management, 2024)
This research aims to analyze the influence of working capital management efficiency (Working Capital Turnover) on Return On Total Assets and the role of Diversification Strategy as a moderating variable on the influence of Working Capital Turnover on Return On Total Assets. The research population is green industry award-winning companies listed on the Indonesia Stock Exchange for the 2019-2021 period. Data obtained from financial reports (Audited). The analysis was carried out using a panel data regression approach with moderating variables used to test the hypotheses in this research. Purpose – The research results show that Working Capital Turnover has a significant negative effect on Return On Total Assets and Diversification Strategy as a moderating variable in the relationship between Working Capital Turnover and Return On Total Assets has a significant positive effect.